2016
DOI: 10.1016/j.celrep.2016.02.081
|View full text |Cite
|
Sign up to set email alerts
|

Structural Model of the Extracellular Assembly of the TCR-CD3 Complex

Abstract: Summary Antigen recognition of peptide-major histocompatibility complexes (pMHCs) by T-cells, a key step in initiating adaptive immune responses, is performed by the T-cell receptor (TCR) bound to CD3 heterodimers. However, the biophysical basis of the transmission of TCR-CD3 extracellular interaction into a productive intracellular signaling sequence remains incomplete. Herein, we used nuclear magnetic resonance (NMR) spectroscopy combined with mutational analysis and computational docking to derive a structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
98
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(108 citation statements)
references
References 60 publications
9
98
1
Order By: Relevance
“…It is therefore conceivable that dynamically driven p/MHC-induced allosteric changes in the constant regions of the TCR, supported both by NMR data presented here and previous hydrogen/deuterium exchange experiments45, could potentiate interactions with CD3γɛ and δɛ, which, according to recent NMR studies, interact only weakly with the free TCR2526.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…It is therefore conceivable that dynamically driven p/MHC-induced allosteric changes in the constant regions of the TCR, supported both by NMR data presented here and previous hydrogen/deuterium exchange experiments45, could potentiate interactions with CD3γɛ and δɛ, which, according to recent NMR studies, interact only weakly with the free TCR2526.…”
Section: Discussionsupporting
confidence: 74%
“…Early NMR studies found the interaction of CD3δɛ with TCR in solution too weak to detect significant chemical shift perturbations41. More recent work found that only a mixture of CD3γɛ and CD3δɛ subunits produced detectable effects on the H3 and H4 helices of the TCR Cβ25, while a subsequent study reported weak but measurable perturbations in both Cα and Cβ upon addition of CD3δɛ or CD3γɛ, respectively26. On the cytoplasmic side, NMR studies have revealed lipid-sensitive conformational changes in the signalling domains of the CD3ζζ homodimer42 and the CD3ɛ subunit38.…”
Section: Discussionmentioning
confidence: 99%
“…These regions include the TCRα AB loop, the TCRβ FG loop, the TCRβ helix 3, and the stalk regions of CD3 . These regions are presumably involved in the interaction of TCRαβ with CD3 and they are not reported to bind to any other protein. Therefore, these mutations hinder the transmission of proper conformational arrangements between the different modules of the TCR, preventing that the TCR adopts the optimal conformation for being triggered.…”
Section: Tcr Triggering Modelsmentioning
confidence: 99%
“…Deuterium/hydrogen exchange and NMR data have shown that the TCRαβ V and C regions are flexible. Upon pMHC binding this flexibility is reduced, and regions implicated in communication with CD3 show large structural changes. These are the Cα AB and the Cβ FG loops, residues near the Cβ αA helix and the Cβ H3 and H4 helices (Figure ).…”
Section: Ligand‐regulated Changes In the Tcr Ectodomainsmentioning
confidence: 99%
“…More recently, NMR characterization of the ␤ chain of a mouse TCR (B4.2.3) specific for an HIV-1 gp120-derived peptide bound to a mouse MHC class I molecule (H2-D d ) revealed amide resonance changes in C␤ upon pMHC ligation (29). Some of these changes were near constant ␤ domain (C␤) residues previously implicated by NMR to interact with CD3 (30,31). Here, we report NMR characterization and molecular dynamics (MD) simulations of both the ␣ and ␤ chains of a human antiviral TCR (A6) that recognizes the Tax antigen (LLFGYPVYV) from human T cell lymphotropic virus-1 (HTLV-1) bound to the human MHC class I molecule HLA-A2 (32).…”
mentioning
confidence: 97%